Hip and Trunk Variables in University Students with and without Recurrent Low Back Pain - BJ Lehecka; Jordin Burleson; Paige Diederich; Morgan Salem; Rachel Schoonover; Jason Tejano (International Journal of Sports Physical Therapy)
# Background